Measuring user emotional response using VFR by applying graceful interaction and physiology tool / Siti Nurnabilah Zailani - Zailani, Siti Nurnabilah (2013)
Graceful interaction is not very well explored by the researchers. Previous researches are mainly focus on gracefulness of speech. While, physiological signals for emotion is very well known among physiologists. It is explored in order to identify people's emotion. Apparently, not much attention has been paid so far on considering graceful elements in designing virtual fitting room. Plus, there is not much consideration on knowing emotional response on virtual fitting room. Therefore, the purpose of this study is to map graceful concept with design elements and analyse user experience based on physiological measurement. For collecting physiological signals, skin conductance is used as physiological measurement in order to measure user emotional response. There are three key findings that have been discovered including types of emotions, combination of design elements, and graph patterns. From the result, it shows that emotions of user on positive dimension side have been produced. The graph of skin conductance also shows the difference number of peaks and graph pattern among participants. Moreover, the findings on graceful concept in design elements also have been found. As a result, the findings of this study can be used by the designer to enhance the design elements of virtual fitting room.